Maternal Intimate Partner Violence Exposure and Autonomic Reactivity: Associations With Positive Parenting. Issue 3 (February 2022) - Molina, Abigail Palmer; Skowron, Elizabeth A.; Hackman, Daniel A.
Intimate partner violence (IPV) can negatively impact parenting, posing a threat both to the wellbeing of mothers and their young children. Parenting may also be influenced by emotion regulation (ER), which can support parents' ability to navigate relational challenges or buffer against the influence of adverse experiences on parenting. Changes in maternal respiratory sinus arrhythmia (RSA) during parent–child interactions have been conceptualized as a psychophysiological index of ER. Competing theoretical models posit that RSA response may mediate or moderate the relation between IPV and parenting or may be independently associated with parenting, however, there is little prior evidence concerning these hypothesized associations. This study examined these associations in a sample of 125 low-income maltreating and comparison mothers and their 3- to 5-year-old children. Dyads completed a moderately challenging laboratory task, and positive parenting and maternal RSA were measured during the task. Maternal verbal IPV exposure, but not physical IPV, was associated with less positive parenting, while greater maternal RSA activation over the task was associated with more positive parenting. Maternal RSA activation did not mediate or moderate the relationship between IPV exposure and parenting, and this association did not differ by whether or not the mother had perpetrated child maltreatment. Consequently, verbal IPV exposure and greater RSA activation independently predicted positive parenting. Results suggest that interventions for IPV-exposed mothers of young children may benefit from ensuring psychological safety and improving maternal ER to promote positive parenting for at-risk children.